Pengaruh Penggunaan Media Internet Terhadap Hasil Belajar Peserta Didik - Fachriadi, Andreansyah; Mugiyono, Mugiyono (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This study limits the use of internet media to the context of learning and focuses solely on analyzing students' cognitive learning outcomes, excluding affective and psychomotor aspects. Students' limited understanding of effective technology use is also considered a constraint. The research aims to examine the influence of internet media utilization on students' final grades. A quantitative correlation approach was employed, with data collected through questionnaires, observations, and documentation. The sample consisted of 43 randomly selected students from SMK Negeri 7 Jakarta Timur. The research instruments included a questionnaire with 20 items for variable X (students' learning outcomes) and variable Y (use of internet media). Analysis using the product moment correlation test revealed an